2020
DOI: 10.1371/journal.pone.0239305
|View full text |Cite
|
Sign up to set email alerts
|

Implicit race attitudes modulate visual information extraction for trustworthiness judgments

Abstract: Black people are still considered to be one of the most stigmatized groups and have to face multiple prejudices that undermine their well-being. Assumptions and beliefs about other racial groups are quite pervasive and have been shown to impact basic social tasks such as face processing. For example, individuals with high racial prejudice conceptualize otherrace faces as less trustworthy and more criminal. However, it is unknown if implicit racial bias could modulate even low-level perceptual mechanisms such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…To finish, we want to highlight some positive developments in first impressions research. Some authors have started to ask whether results obtained using White faces replicate when stimulus sets include faces of colour [30,56,58,[122][123][124]. A particularly good example is a recent study described by Jones et al [56].…”
Section: Positive Developmentsmentioning
confidence: 99%
“…To finish, we want to highlight some positive developments in first impressions research. Some authors have started to ask whether results obtained using White faces replicate when stimulus sets include faces of colour [30,56,58,[122][123][124]. A particularly good example is a recent study described by Jones et al [56].…”
Section: Positive Developmentsmentioning
confidence: 99%
“…Although much research has been conducted to establish which distinct facial pieces of information evokes trustworthiness perception in the perceiver [ 30 , 31 ], only few studies have investigated how the spatial resolution in which such pieces of information are visually processed impacts trustworthiness ratings [ 32 , 33 ]. These studies indicated that the eye and eyebrow region modulates trustworthiness judgments when their HSF components are available, while the mouth plays a role when revealed in its LSF components [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we applied the spatial filtering approach to the investigation of trustworthiness perception to explore whether the information on which trustworthiness judgments are based differs according to participants’ expertise with specific face types. To the best of our knowledge, so far only two studies adopted this same approach [ 32 , 34 ]. The first one tested for the modulatory effects of image spatial frequency filtering on the amygdala response to very trustworthy and very untrustworthy faces using fMRI [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to them being deemed no longer relevant or informative (Lockwood & Kunda, 1997;Brown et al, 1992) or because some participants may be motivationally driven to ignore the potentially socially sensitive consequences of interracial comparisons. Furthermore, the evaluative dimension of trustworthiness may be too closely related to the ethnic categories used in the current work, with recent research highlighting that the visual cues of facial trustworthiness may be processed differently across ethnic lines (Charbonneau et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Although a sound possible explanation for the unexpected data pattern, these post-hoc explanations should be considered as such and with some caution as to not give them too much weight, as many other factors may have played a role. For instance, the trustworthiness dimension may be confounded with the ethnicity manipulation to some extent, as recent work has highlighting that this dimension may be processed differently across ethnic lines (Charbonneau et al, 2020).…”
Section: Discussionmentioning
confidence: 99%